Delayed vs. immediate placement of restorative materials over Biodentine and RetroMTA: a micro-shear bond strength study - Ozge Celiksoz; Ozgur Irmak (BMC, 2024)
Abstract Background The aim of the present study was to investigate the micro-shear bond strength (µSBS) of various restorative materials applied on two different fast-setting calcium silicate-based materials and to evaluate the effect of restoration time on µSBS. Methods A total of 180 acrylic blocks with a cavity in the center were randomly divided into 2 main groups according to the capping material to be used (Biodentine or RetroMTA). The specimens were also randomly divided into 3 groups according to the restoration time (3 min, 12 min, 24 h). After the specified waiting periods, glass hybrid material (EQUIA Forte HT), resin composite (Filtek Z550) and light-cured calcium silicate material (Theracal LC) were placed on the specimens with tygon tubes. The specimens were kept for 24 h and then subjected to µSBS test. Statistical analysis was performed by 3-way ANOVA followed by Tukey test for pairwise comparisons (α = 0.05). Results There is a statistically significant difference (p < 0.05) between the µSBS values obtained by applying resin composite on RetroMTA after different setting times (24 h > 12 min > 3 min). The µSBS obtained for the Biodentine-resin composite at the end of the 3 min setting time is significantly lower (p < 0.05) than the µSBS values at 12 min and 24 h. For both calcium silicate cements, at the end of all time periods, the µSBS obtained when resin composite was applied at the end was higher than the other materials (p < 0.05). Conclusions For Biodentine-resin composite bonding, the manufacturer's recommendation of 12 min can be considered an appropriate time, whereas for RetroMTA-resin composite bonding, the µSBS increased as the waiting time increased. Regardless of the waiting time, it is recommended to prefer direct composite resin restoration over Biodentine and RetroMTA.